The Lived Experiences of Nurses and Physicians Caring for Children with Complex Care Needs in Paediatric Intensive Care Units during the First Eighteen Months of the COVID-19 Pandemic. - Hill, Katie (Trinity College Dublin. School of Nursing & Midwifery. Discipline of Nursing, 2023)
The global pandemic caused by COVID-19 has affected the health and wellbeing of children across the world. Children with complex care needs (CCNs) have a range of health and social care needs, including physical, developmental, behavioural and/or emotional conditions, which can put them at risk of more severe illness and complications from COVID-19. Due to their medical complexity, this cohort of children accounts for an increasing proportion of paediatric intensive care unit (PICU) admissions worldwide. There is limited research conducted about the impact of the COVID-19 pandemic on children with CCNs; instead, research has focused primarily on the impact of care delivery in the home as a result of public health restrictions. However, there is a scarcity of literature about care delivery for this cohort of children in paediatric intensive care units (PICUs). The aim of this research was to explore and understand the meaning given to care delivery to children with CCNs in PICUs by nurses and physicians during the first 18 months of the COVID-19 pandemic. The first of three objectives was to examine experiences internationally of caring for children with CCNs in PICUs during the first 18 months of the COVID-19 pandemic. The second objective was to articulate what has been learned from experiences during this specific time frame of the COVID-19 pandemic, to support ongoing care in PICUs for this population of children. The final objective was to present implications for the enhancement of care in PICUs following the pandemic, including changes to care delivery. A hermeneutic phenomenological approach, guided by the work of van Manen (1990), underpinned this research. Following ethical approval, purposive sampling was used to gather data from nurses and physicians who were working in PICUs during the first 18 months of the COVID-19 pandemic. Online interviews were conducted using Zoom in adherence with public health advice against travel and face-to-face meetings during this time in the pandemic. Van Manen?s method for data analysis was used to analyse the data and to deduce the key essential themes (van Manen 2014a). The data from the interviews with 18 nurses and 22 physicians was analysed together as the overall aim of the research was to explore and understand the meaning given to care delivery to children with CCNs in PICUs by nurses and physicians during the first 18 months of the COVID-19 pandemic. Five themes and eight sub-themes emerged from data analysis. These sub- themes were: provision of care to children with CCNs in PICUs; decision- making affecting children with CCNs in PICUs; effect of COVID-19 on children with CCNs and on clinical activity in PICUs; visiting restrictions within PICUs for children with CCNs; relationships between healthcare professionals and families of children with CCNs; learning from COVID-19 in the context of children with CCNs in PICUs; changes in day-to-day practices due to COVID-19 relating to children with CCNs; and allocation of resources in PICUs for children with CCNs. Overall, participants experienced very little difference in their care delivery to children with CCNs in PICUs during the first 18 months of the COVID-19 pandemic. This research provided a unique insight into the nurses? and physicians? lived experiences of delivering care to children with CCNs in PICUs during the first 18 months of the COVID-19 pandemic. The presentation and interpretation of findings - alongside the in-depth discussion - resulted in identification of implications for research, education and policy, including the use of telemedicine to enhance care for children with CCNs in PICUs. Through the exploration of these lived experiences, key elements can be extracted for progressing care delivery in a PICU. Considerations for further research in this area have also been identified.
APPROVED
Keywords: COVID-19; children with complex care needs; paediatric intensive care units